A chemical vapour deposition reactor for carbon fibre surface treatment. - Abdul Rashid, Suraya; Yunus, Robiah; Shamsuddin, Suriani (2008)

(untitled)
A chemical vapor deposition reactor for carbon fiber surface treatment comprises a quartz tube with an inlet and an outlet which is spinning across horizontally within a furnace; a hydrocarbon source storage means connected to the inlet which benzene is carried by hydrogen gas derived from a hydrogen gas delivering means into quartz tube and a significant amount of catalyst precursor is placed within the quartz tube and an exhausted by products whereby the catalyst precursors are turned into gases under heating within the quartz tube which is then reduced to atomic ions under the high reaction temperature to catalyze growth of CNTs from the hydrocarbon source onto surfaces of the carbon fibers placed within the quartz tube during the whiskerization process.